RELUS: EFFECTIVE TECHNIQUE OF TEACHING ENGLISH FOR THE SOCIETY MEMBERS - Sudipa, I Nengah (Lingual Journal of Language and Culture; Vol 1 No 1 (2016)DO - 10.24843/LJLC.2016.v01.i01.p03, 2016)
This article aims at introducing the effective Communicative approach, with RELUS techniques applied in the process of English course for the members of the society. The data derived from the impression conducting such course in the year of 2015, and collected by direct observation and random interview. The course was attended by 40 members of Pokdarwis Mekar Bhuana in Pangsan Village, Petang subdistrict, Badung Regency. The course materials were about English functions and English for Tourism. The speaking materials were delivered in terms of conversational process using the techniques of: RELUS (R=read, LU =look up, S=say). The steps for each session were: orientation, drills, feedback and continuation. The result showed that generally all participants manage to speak actively to welcome the English speaking tourists coming to their respective villages.
Keywords: Pokdarwis, RELUS, Mekar Bhuana